Transformative Learning and Identity. (April 2014) - Illeris, Knud
Transformative learning has usually been defined as transformations of meaning perspectives, frames of reference, and habits of mind—as proposed initially by Jack Mezirow. However, several authors have found this definition too narrow and too cognitively oriented, and Mezirow has later emphasized that emotional and social conditions are also important. Thus, there is a need for a broader, more up-to-date, and still significant definition. This article suggests that the target area of transformative learning should be defined by the term "identity, " which explains what this term implies, argues why it is the best possible choice, and gives examples of how the concepts of transformative learning and identity can mutually enrich each other and lead to new understandings in both of these areas.